Injection Timing Effect on Emisson Characteristic of a Dual-Fuel Diesel Engine - Dyas Isnaen Ilham; Fathin Muhammad Mahdhudhu (Fakultas Teknik UPN Veteran Jakarta, 2026)
The maritime industry is facing increasingly stringent emission regulations, driving the development of cleaner combustion technologies such as dual-fuel diesel engines fueled by natural gas. Among various operational parameters, pilot diesel injection timing plays a crucial role in determining combustion characteristics and exhaust emissions. This study numerically investigates the effect of Start of Injection (SOI) on the emission characteristics of a methane dual-fuel diesel engine using three-dimensional computational fluid dynamics (CFD) simulations in ANSYS Forte. A 45° sector model with a re-entrant piston bowl geometry was employed to represent the combustion chamber while maintaining computational efficiency. The simulations were conducted at an engine speed of 1335 rpm by varying the pilot diesel SOI from −37.5° to −27.5° CA bTDC. The results indicate that retarding the injection timing significantly increases incomplete combustion products, with CO emissions rising from 3314.75 ppm to 11989.00 ppm and UHC emissions increasing from 490.87 ppm to 2557.44 ppm. Conversely, NOx emissions decrease from 938.59 ppm to 479.03 ppm because delayed combustion reduces the peak in-cylinder temperature and suppresses thermal NOx formation. These findings demonstrate a clear emission trade-off associated with injection timing, where reducing NOx is accompanied by increases in CO and UHC emissions. Therefore, an appropriate SOI should be selected to achieve a balanced compromise between combustion efficiency and exhaust emission performance in methane dual-fuel diesel engines.